Co-metabolic formation of substituted phenylacetic acids by styrene-degrading bacteria - Oelschlägel, Michel; Kaschabek, Stefan R.; Zimmerling, Juliane; Schlömann, Michael; Tischler, Dirk (Biotechnology reports (Amsterdam, Netherlands), 2015)
[Display omitted] •Styrene degradation via phenylacetic acid was shown for the strains described.•Co-metabolic transformation of substituted styrenes was shown.•Formation of several phenylacetic acids, e.g. ibuprofen, was reported.•α-Methylated substrates were transformed enantioselectively with an ee of up to 40%.•Pseud. fluorescens ST was identified as promising biocatalyst for phenylacetic acids. Some soil bacteria are able to metabolize styrene via initial side-chain oxygenation. This catabolic route is of potential biotechnological relevance due to the occurrence of phenylacetic acid as a central metabolite. The styrene-degrading strains Rhodococcus opacus 1CP, Pseudomonas fluorescens ST, and the novel isolates Sphingopyxis sp. Kp5.2 and Gordonia sp. CWB2 were investigated with respect to their applicability to co-metabolically produce substituted phenylacetic acids. Isolates were found to differ significantly in substrate tolerance and biotransformation yields. Especially, P. fluorescens ST was identified as a promising candidate for the production of several phenylacetic acids. The biotransformation of 4-chlorostyrene with cells of strain ST was shown to be stable over a period of more than 200 days and yielded about 38mmolproductgcelldryweight−1 after nearly 350 days. Moreover, 4-chloro-α-methylstyrene was predominantly converted to the (S)-enantiomer of the acid with 40% enantiomeric excess.